Study on a New Steering Mechanism for Point-the-Bit Rotary Steerable System. (22nd February 2014) - Li, Yuanzhi; Niu, Wentie; Li, Hongtao; Luo, Zhenjun; Wang, Lina
Abstract : This paper presents a novel steering mechanism embedded in a point-the-bit rotary steerable system (RSS) for oilfield exploitation. The new steering mechanism adopts a set of universal joints to alleviate the high alternative strain on drilling mandrel and employs a specially designed planetary gear small tooth number difference (PGSTD) to achieve directional steering. Its principle and characteristics are explained and examined through a series of analyses. First, the eccentric displacement vector of the offset point on the drilling mandrel is formulated and kinematic solutions are established. Next, structural design for the new steering mechanism is addressed. Then, procedures and program architectures for simulating offset state of the drilling mandrel and motion trajectory of the whole steering mechanism are presented. After that, steering motion simulations of the new steering mechanism for both 2D and 3D well trajectories are then performed by combining LabVIEW and SolidWorks. Finally, experiments on the steering motion control of the new steering mechanism prototype are carried out. The simulations and experiments reveal that the steering performance of the new steering mechanism is satisfied. The research can provide good guidance for further research and engineering application of the point-the-bit RSS.